Wdrażanie monitoringu finansowego w jednostkach administracyjnych zasobami mieszkaniowymi - Dyczkowski, Tomasz (Implementation of financial monitoring in housing administration, 2006)
Pressure on efficiency of operations along with serious problems of tenants' indebtedness make an idea of financial monitoring worth considering by housing administrators. The first part of the paper presents five stages of implementation of financial monitoring in the above-mentioned group of business entities. An analysis of information requirements and current information system in an exemplary unit is carried out subsequently. Eventually, the author presents possibilities of application of financial monitoring in systematic observation of cash flows related with administration of housing resources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1125, s. 38-46